2003
DOI: 10.1074/jbc.m301436200
|View full text |Cite
|
Sign up to set email alerts
|

Secretory IgA N- and O-Glycans Provide a Link between the Innate and Adaptive Immune Systems

Abstract: Secretory IgA (SIgA) is a multi-polypeptide complex consisting of a secretory component (SC) covalently attached to dimeric IgA containing one joining (J) chain. We present the analysis of both the N-and O-glycans on the individual peptides from this complex. Based on these data, we have constructed a molecular model of SIgA1 with all its glycans, in which the Fab arms form a T shape and the SC is wrapped around the heavy chains. The O-glycan regions on the heavy (H) chains and the SC N-glycans have adhesin-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
327
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 303 publications
(343 citation statements)
references
References 74 publications
11
327
1
4
Order By: Relevance
“…We found that carbohydrates present on the ␣ chain could not be removed following exposure to N-glycosidase F. This observation is consistent with the masking of N-glycan residues by SC in the context of the whole SIgA molecule (20,51). It is plausible that these noncleavable carbohydrates would be responsible for the various residual interaction observed upon incubation of Gram-positive bacteria with SIgAdg.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…We found that carbohydrates present on the ␣ chain could not be removed following exposure to N-glycosidase F. This observation is consistent with the masking of N-glycan residues by SC in the context of the whole SIgA molecule (20,51). It is plausible that these noncleavable carbohydrates would be responsible for the various residual interaction observed upon incubation of Gram-positive bacteria with SIgAdg.…”
Section: Discussionsupporting
confidence: 73%
“…Because SIgA and SC are highly glycosylated proteins (19,20), we performed deglycosylation cleaving all types of N-branched glycan residues bound to asparagine. Contrary to most of other methods, N-glycosidase F removes carbohydrate residues by preserving the conformational structure of the protein (23).…”
Section: Siga Binds Bacteria In a Fab-and Fc-independent Manner-mentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, IgA1 with truncated O-glycans in the hinge region is prone to self-aggregation and forms immune complexes with the IgG antibody against the hinge region of IgA1. 37 As such, the O-linked glycans at the hinge region may affect the stability and function of Fc fusion proteins. 37 In the CTLA4-Ig fusion proteins, we detected the O-linked glycans on T8-9 (SSDKTHTSPPSPA-PELLGGSSVFLF PPKPK).…”
Section: Resultsmentioning
confidence: 99%
“…37 As such, the O-linked glycans at the hinge region may affect the stability and function of Fc fusion proteins. 37 In the CTLA4-Ig fusion proteins, we detected the O-linked glycans on T8-9 (SSDKTHTSPPSPA-PELLGGSSVFLF PPKPK). As shown in Figure 3D, at the lower (6v) MS level, we confirmed the peptide sequence utilizing collision-induced dissociation (CID) for glycopeptide fragmentation.…”
Section: Resultsmentioning
confidence: 99%